Analisis Kinerja Sekretariat DPRD Pasca Berlakunya Peraturan Wali Kota Nomor 5 Tahun 2023 di Kota Banjarbaru Kalimantan Selatan - Asmarabia; Kristanto, Budi (Universitas Muhammadiyah Sorong, 2023)
The performance target of the DPRD Secretariat is to provide satisfactory services and facilities for DPRD leaders and members and work together to achieve SKPD goals. The Banjarbaru City Regional People's Representative Council Secretariat carries out its main duties and functions to support all operational activities of DPRD leaders and members to guide several regulations so that they do not conflict with applicable legal norms. Description of the main duties and functions of the Banjarbaru City DPRD secretariat, there are changes to the Organizational Structure and Work Procedures (SOTK) which are determined and implemented in 2023. This research aims to analyze the effectiveness of the DPRD Secretariat's performance with the latest Mayor's Regulation Number 5 of 2023 for Banjarbaru City. In carrying out this analysis, the author used a normative qualitative approach (literature) and participant observation. The research results show that Mayor Regulation No. 5 of 2023 has returned all functional positions resulting from the alignment into structural positions again. With the enactment of Mayor's Regulation Number 5 of 2023, the DPRD Secretariat can perform optimally by achieving SKPD targets through strategic targets and Key Performance Indicators. This is because; 1) there is clarity of responsibility; 2) have a clear position; 3) have a clear relationship path; and 4) The duties and functions of each have been clearly described (job description).